Finance of oversea trade - Syrett, W. W. (London, Pitman, 1964)
The book explains all the processes involved in undertaking the international trade and those that are involved in it
First published in 1937 under title: Practice and finance of foreign trade.
Includes index
oif 12/02/2019
Loans
Keywords: International trade; Foreign exchange; Commerce; Great Britain